Calosoma (Coleoptera: Carabidae) biological control introductions to Hawaiʻi: Taxonomic ignorance and confusion lead to an unexpected result - James K. Liebherr; Janis N. Matsunaga; Ann E. Hajek (Biological Control)
From 1897 until 1957, beetles of the genus Calosoma L. (Coleoptera: Carabidae) were repeatedly introduced to the Hawaiian Islands as predators of nutgrass armyworm, Spodoptera exempta (Walker), armyworm, Mythimna unipuncta (Haworth), and lawn armyworm, Spodoptera mauritia (Boisduval). Through examination of institutional voucher specimens, archival field notes, and the literature, we document failed biological control introductions of eight flight-capable Calosoma species: C. calidum (F.), C. frigidum Kirby, C. marginale Casey, C. peregrinator Guérin-Méneville, C. prominens LeConte, C. protractum LeConte, C. semilaeve LeConte, and C. senegalense Dejean. In contrast, the vestigially-winged C. anthracinum Dejean, a rarely collected Mexican species never intentionally introduced, is the only Calosoma currently resident in Hawaiʻi. Calosoma anthracinum was misidentified initially as C. semilaeve, and thereafter misidentified as Calosoma blaptoides tehuanacum Lapouge. Both C. anthracinum and C. protractum were collected sympatrically at Cuernavaca, Morelos, Mexico during Hawaiʻi-based explorations, and we hypothesize that they were introduced together as a species mixture in a 1923 release made at Waikiʻi, Parker Ranch, Hawaiʻi Island. Calosoma anthracinum was little known to taxonomists at that time due to its limited native distribution, rarity in institutional collections, and absence from taxonomic keys, leading to repeated misidentifications. Calosoma peregrinator and C. prominens, two abundant, sympatric species from the Sonoran and Chihuahuan Deserts, were also taxonomically confused over this period, resulting in mixed-species Hawaiian introductions. Three species that failed to establish upon introduction—C. marginale, C. peregrinator and C. semilaeve—have been intercepted as singletons or pairs of individuals decades later, without apparent establishment. Calosoma beetles’ ecological requirements, dispersal abilities, introduction histories, and native ranges and associated climate are compared among species, the only unique characteristic of the successful colonist being flightlessness. The history of Hawaiian Calosoma introductions illustrates the need for robust and accessible classifications based on accurately determined specimens as well as comprehensive understanding of the biological attributes and habitat requirements of candidate biological control agents.